2019
DOI: 10.1158/1078-0432.ccr-18-1627
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tumor Microenvironment and Host State: Implications for Immunotherapy

Abstract: Glioblastoma (GBM) is a highly lethal brain tumor with poor responses to immunotherapies that have been successful in more immunogenic cancers with less immunosuppressive tumor microenvironments (TME). The GBM TME is uniquely challenging to treat due to tumor cellextrinsic components that are native to the brain, as well as tumor-intrinsic mechanisms that aid in immune evasion. Lowering the barrier of immunosuppression by targeting the genetically stable tumor stroma presents opportunities to treat the tumor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
197
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(219 citation statements)
references
References 94 publications
3
197
0
Order By: Relevance
“…Moreover, profound immunosuppression occurs in the tumor microenvironment, particularly in the context of cell-mediated immunity [31], which is driven by an array of cytokines, such as prostaglandin E2, transforming growth factor beta (TGF-β), matrix metallopeptidase 9, IL-10, programmed death-ligand 1 (PD-L1), granulocyte colony stimulating factor, VEGF, and S100A4 [18,31,33,52,53]. At a mechanistic level, most proposed pathways to mediate immunosuppression in GBM are those involving signal transducer and activator of transcription 3 (STAT-3) [54,55], phosphoinositide 3 kinase, Ras-mitogen-activated protein kinase, wingless-related integration site/β-catenin, and indolamine 2, 3-dioxygenase [56].…”
Section: Tans In Glioma Progressionmentioning
confidence: 99%
“…Moreover, profound immunosuppression occurs in the tumor microenvironment, particularly in the context of cell-mediated immunity [31], which is driven by an array of cytokines, such as prostaglandin E2, transforming growth factor beta (TGF-β), matrix metallopeptidase 9, IL-10, programmed death-ligand 1 (PD-L1), granulocyte colony stimulating factor, VEGF, and S100A4 [18,31,33,52,53]. At a mechanistic level, most proposed pathways to mediate immunosuppression in GBM are those involving signal transducer and activator of transcription 3 (STAT-3) [54,55], phosphoinositide 3 kinase, Ras-mitogen-activated protein kinase, wingless-related integration site/β-catenin, and indolamine 2, 3-dioxygenase [56].…”
Section: Tans In Glioma Progressionmentioning
confidence: 99%
“…Brain tumors, including primary and metastatic tumors, are among the most feared of all forms of cancer with very limited treatment options and a poor prognosis. [17][18][19] Malignant cerebral gliomas, the most common primary tumor in the CNS, comprising 80% of all malignant primary brain tumors, 20 have a strong tendency to infiltrate. 21 Nevertheless, metastatic brain tumors are the most frequently occurring intracranial tumors.…”
Section: Introductionmentioning
confidence: 99%
“…However, GBM is thought to have a low mutational burden and to be immunologically cold. 21 Moreover, other studies have reported that immunotherapies can alter the tumour microenvironment in GBM, which may influence patients' response to treatment and culminate in benefits from combined therapies. 15,22 The diagnosis of GBM is currently based on imaging techniques and tissue biopsies.…”
Section: Introductionmentioning
confidence: 99%